International Handbook of Research in Arts Education - Bresler, Liora (Springer International Handbooks of Education, 2007)
Providing a distillation of knowledge in the various disciplines of arts education (dance, drama, music, literature and poetry and visual arts), the Handbook synthesizes existing research literature, helps define the past, and contributes to shaping the substantive and methodological future of the respective and integrated disciplines of arts education. While research can at times seem distant from practice, the Handbook aims to maintain connection with the lived practice of art and of education, capturing the vibrancy and best thinking in the field of theory and practice. The Handbook is organized into 13 sections, each centering on a major area or issue in arts education research. These areas include: History of arts education, curriculum, evaluation, cultural centers, appreciation, composition, informal learning, child culture, creativity, the body, spirituality, and technology. The individual chapters address cross-cultural research related to the central theme of the section from the perspectives of the particular arts discipline. Interludes provide reflective thoughts on the theme.